Applications and Recent Advances in 3D Bioprinting Sustainable Scaffolding Techniques - Xianyao Li; Jianyu Ren; Yubo Huang; Li Cheng; Zhengbiao Gu (Molecules)
In recent years, with the rapid advancement of 3D printing technology, its applications have expanded across numerous fields. Notably, the fabrication of scaffolds using 3D printing has emerged as a major research focus. Researchers are investigating the properties of various printing materials and tailoring their uses for specific applications. This article reviews the characteristics and applications of different biomaterials printed by 3D technology, such as gelatin, sodium alginate, and starch, highlighting their contributions to the expanding field of 3D-printed biomaterials. Through the comparison in this review, it can be observed that the starch scaffold not only has a lower price but also can be modified to achieve multifunctionality, better meeting the performance requirements in more fields.